Use of the Phylobone database for the annotation of bone extracellular matrix proteins in reindeer (Rangifer tarandus) - Sánchez-Reverté, Alba (Sage, 2026)
Bone extracellular matrix (ECM) proteins play a key role in bone formation and regeneration, including structural and regulatory functions. The Phylobone database consists of 255 ECM protein groups from 39 species and can be used to support bone research. Here, we gathered bone ECM proteins from reindeer (Rangifer tarandus), a member of the Cervidae family. The importance of reindeer lies in their ability to regenerate their antlers, in both male and female individuals. Protein sequences were extracted from the National Center for Biotechnology Information's repository and selected by homology searches. We identified 215 proteins and their corresponding functional domains, which are putatively present in the bone ECM of reindeer. Protein sequence alignments have shown a high degree of conservation between R. tarandus and other members of the Cervidae family. This update expands the Phylobone database and shows that it is a useful resource for the preliminary annotation of bone ECM proteins in novel proteomes.